Avon Brazil: Optimization of Logistics Processes in a Direct Selling Company - Medeiros,Fabio (2021)
ABSTRACT This case study aims to develop in each student analytical competencies by evaluating current logistics processes and, from this understanding, to use the knowledge gained on tools and theories of continuous improvement to propose solutions and discuss strategic alternatives for the company to improve its processes. Efficiency in logistics operations plays a key role in the results of direct sales companies because there are thousands of customers and daily deliveries that bring complexity to the process. The new Supply Chain Director took over the position in a difficult period of falling market in the country. Thereby he implemented internal discussions to evaluate the status of various processes and to engage leadership. He intends to find ways to improve logistics processes through capital investments or by using continuous improvement tools that could provide cost reductions and increase service levels. The case can be used in undergraduate courses, graduate courses, and also in professional education in themes related to business management, supply chain, logistics, and industrial operations.